Gender parity in scientific authorship in a National Institute for Health Research Biomedical Research Centre: a bibliometric analysis - Shah, SGS; Dam, R; Milano, MJ; Edmunds, LD; Henderson, LR; Hartley, CR; Coxall, O; Ovseiko, PV; Buchan, AM; Kiparoglou, V (BMJ Publishing Group, 2021)
Objective: Scientific authorship is a vital marker of achievement in academic careers and gender equity is a key performance metric in research. However, there is little understanding of gender equity in publications in biomedical research centres funded by the National Institute for Health Research (NIHR). This study assesses the gender parity in scientific authorship of biomedical research.